2019
DOI: 10.1093/jas/skz091
|View full text |Cite
|
Sign up to set email alerts
|

Integrated miRNA–mRNA transcriptomic analysis reveals epigenetic-mediated embryonic muscle growth differences between Wuzhishan and Landrace pigs1

Abstract: Pig is one of the major dietary protein sources for human consumption, from which muscle is the largest protein origin. However, molecular mechanisms concerning early porcine embryonic muscle development distinctions between pig breeds are still unclear. In this study, an integrated analysis of transcriptome and miRNAome was conducted using longissimus dorsi muscle of 4 early embryonic stages around the primary myofiber formation time (18-, 21-, 28-, and 35-d post coitus) from 2 pig breeds (Landrace [LR] and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Multiple genes are targeted by a single miRNA and multiple miRNAs can target a single gene, which makes miRNAs a major player in gene regulation and important biological processes, including fetal and placental development [9][10][11]. Several studies have showed the role of miRNAs and their target genes in skeletal muscle development at different prenatal and postnatal stages across different breeds of pigs [7,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple genes are targeted by a single miRNA and multiple miRNAs can target a single gene, which makes miRNAs a major player in gene regulation and important biological processes, including fetal and placental development [9][10][11]. Several studies have showed the role of miRNAs and their target genes in skeletal muscle development at different prenatal and postnatal stages across different breeds of pigs [7,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The number and density of myoblasts and myogenesis intensity also varies with the animal species and breed. For instance, prenatal myogenesis intensity and the number of myoblasts are higher in fat pig breeds compared to lean pig breeds [7,14,20]. In addition to variation in myogenesis intensity, the expression of miRNAs and genes regulating muscle development also differs across different pig breeds.…”
Section: Introductionmentioning
confidence: 99%
“…ACTNs (α-actinins) are widely expressed cytoskeleton proteins that cross-link actin filaments at the adherens junctions in epithelial and focal adhesions at the leading edge of migrating cells [ 55 , 56 ], and play a key role in the maintenance and regulation of the cytoskeleton. In mammalian cells, there are four kinds of ACTNs, which are the components of all three kinds of stress fibers (ventral stress fibers, dorsal stress fibers, and transverse arcs) [ 57 , 58 ]. ACTN 3 is a prominent actin filament associated protein that is expressed in skeletal muscle [ 59 ], and its function is to maintain the microfilament spacing at the Z-disc.…”
Section: Discussionmentioning
confidence: 99%
“…A single miRNA can regulate the expression of multiple genes through post-transcriptional repression and epigenetic regulation, making miRNAs the major regulators of gene expression [ 28 , 29 , 30 , 31 , 32 ]. Several studies have shown the role of miRNAs and their target genes in skeletal muscle growth and development at different prenatal and postnatal stages across different breeds of pigs [ 23 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%